The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/liv.13103
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence and virological response rates in hepatitis C virus infected persons treated with sofosbuvir‐based regimens: results from ERCHIVES

Abstract: Sofosbuvir-based treatment regimens are highly effective in achieving SVR12. This efficacy is not significantly affected when treated persons receive less than a full prescribed course of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…These results show how we have successfully simplified HCV management in a high-burden setting, and confirm under operational conditions the high efficacy of DAAs that has previously been reported in the controlled environment of clinical trials. [1619]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show how we have successfully simplified HCV management in a high-burden setting, and confirm under operational conditions the high efficacy of DAAs that has previously been reported in the controlled environment of clinical trials. [1619]…”
Section: Discussionmentioning
confidence: 99%
“…The new all-oral treatment regimen, with the exception of GT1 (which requires pegylated IFN on top of the SOF-RBV combination), is highly tolerable with documented limited adverse events in clinical trials. [1619] The VALENCE study, a multicenter Phase 3 trial in Europe showed that the SOF-RBV regimen for 24 weeks in GT3 patients had an SVR12 of 85%. [18] Conventional management relying on an IFN-based treatment regimen over a prolonged time period [10] resulted in general SVR rates of 42–93% for all genotypes, showing only moderate efficacy for the combination of pegylated IFN with Ribavirin in multiple randomized control trials.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a retrospective cohort study among HCV‐infected persons in the Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES) database. ERCHIVES is a large, well‐established national cohort of HCV‐infected and uninfected Veterans and has been described . All HCV‐infected Veterans at any of the nation‐wide Department of Veterans Affairs (VA) medical facilities with a positive HCV antibody test between 2002 and 2016 were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Treating HCV has recently been revolutionized by the introduction of effective direct acting antivirals (DAA) which have made possible interferon-free treatment with a very high success rate (5,6). In fact, there is now a prospect for HCV elimination (7).…”
Section: Introductionmentioning
confidence: 99%